Development of Nanostructured Water Treatment Membranes Based on Thermotropic Liquid Crystals: Molecular Design of Sub‐Nanoporous Materials. Issue 1 (18th December 2017) - Sakamoto, Takeshi; Ogawa, Takafumi; Nada, Hiroki; Nakatsuji, Koji; Mitani, Masato; Soberats, Bartolome; Kawata, Ken; Yoshio, Masafumi; Tomioka, Hiroki; Sasaki, Takao; Kimura, Masahiro; Henmi, Masahiro; et al.
Abstract: Supply of safe fresh water is currently one of the most important global issues. Membranes technologies are essential to treat water efficiently with low costs and energy consumption. Here, the development of self‐organized nanostructured water treatment membranes based on ionic liquid crystals composed of ammonium, imidazolium, and pyridinium moieties is reported. Membranes with preserved 1D or 3D self‐organized sub‐nanopores are obtained by photopolymerization of ionic columnar or bicontinuous cubic liquid crystals. These membranes show salt rejection ability, ion selectivity, and excellent water permeability. The relationships between the structures and the transport properties of water molecules and ionic solutes in the sub‐nanopores in the membranes are examined by molecular dynamics simulations. The results suggest that the volume of vacant space in the nanochannel greatly affects the water and ion permeability. Abstract : Filtration membranes with 1D or 3D ordered ionic sub‐nanopores prepared from thermotropic liquid crystals show unique salt rejection properties and applicable water permeability. Molecular dynamics simulation show the effects of the ionic sub‐nanopores on transport of water molecules and ionic solutes in the pores. Membranes with liquid‐crystalline ordered structures have great potential for highly selective separation.